Lothagam : the dawn of humanity in eastern Africa - Leakey, Meave G.; Harris, John M. (John Michael) (Columbia University Press, 2003)
Located at the southwest corner of Lake Turkana in northern Kenya, Lothagam represents one of the most important intervals in African prehistory. Early human remains are restricted in distribution to Africa and the acquisition of an upright bipedal striding gait, the hallmark of humanity, appears to be at least circumstantially linked to the reduction of equatorial forests and the spread of grasslands on that continent. The diverse Lothagam fauna documents the end-Miocene transition from forested to more open habitats that were exploited by grazing horses and antelopes, hippos, giant pigs, and true elephants. It also includes spectacularly complete fossil carnivore skeletons and some of the oldest human remains.